The Impact of Parental Divorce on The Behavior of Christian Children - Situmorang, Dinar Marlinang V.; Panjaitan, Binur; Saragih, Ratna; Samosir, Lustani (the International Journal of Education, Theology, and Humanities, 2024)
The background of the problem in this study is the impact or consequences of parental divorce on children's psychology, where children feel depressed because of lack of attention, lack of affection and children become lonely, sad, shy and quiet even their daily needs are not fulfilled, both in terms of material, affection, attention from both parties, both from the father and the mother. The formulation of the problem in this study is what are the factors that cause divorce that occurs in the Tarutung District Court, and what is the impact of parental divorce on the behaviour of children who carry out divorce in the Tarutung District Court. The purpose of this research is to find out what factors cause divorce that occurs in Tarutung District Court, and to find out what the impact of parental divorce is on children's behaviour. The purpose of this research is to find out what are the factors that cause divorce that occurs in Tarutung District Court, and to find out what is the impact of parental divorce on the behaviour of children whose parents experience divorce. This research is a type of field research (Field Research) with a qualitative approach using descriptive analysis. The sources of this research are 4 families who experienced the divorce process at the Tarutung District Court. The results obtained from this study indicate that the factors causing parental divorce in Tarutung District Court are due to several factors, namely economic factors, infidelity factors, husbands rarely return home, and excessive jealousy. And the impact of parental divorce on the behaviour of children whose parents divorce in Tarutung District Court often experience negative behavioural impacts, namely causing shame, sadness, children become quiet, and children become irritable.